Effectiveness of Liquid-Liquid Extraction, Solid Phase Extraction, and Headspace Technique for Determination of Some Volatile Water-Soluble Compounds of Rose Aromatic Water - Hale Seçilmiş Canbay (International Journal of Analytical Chemistry)
Steam distillation is used to isolate scent of rose flowers. Rose aromatic water is commonly used in European cuisine and aromatherapy besides its use in cosmetic industry for its lovely scent. In this study, three different sampling techniques, liquid-liquid extraction (LLE), headspace technique (HS), and solid phase extraction (SPE), were compared for the analysis of volatile water-soluble compounds in commercial rose aromatic water. Some volatile water-soluble compounds of rose aromatic water were also analyzed by gas chromatography mass spectrometry (GCMS). In any case, it was concluded that one of the solid phase extraction methods led to higher recoveries for 2-phenylethyl alcohol (PEA) in the rose aromatic water than the liquid-liquid extraction and headspace technique. Liquid-liquid extraction method provided higher recovery ratios for citronellol, nerol, and geraniol than others. Ideal linear correlation coefficient values were observed by GCMS for quantitative analysis of volatile compounds (r2≥0.999). Optimized methods showed acceptable repeatability (RSDs < 5%) and excellent recovery (>95%). For compounds such as α-pinene, linalool, β-caryophyllene, α-humulene, methyl eugenol, and eugenol, the best recovery values were obtained with LLE and SPE.